Epidemiology of enteroparasitosis in schoolchildren from Manabí, Ecuador - Jazmin Elena Castro Jalca; Leonardo Mera Villamar; Mercedes Schettini Álava (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2020)
Intestinal parasitoses are infections caused by helminths, chromists, and protozoa. The majority are transmitted by the fecal - oral route, especially by ingestion of water and food contaminated with infecting forms. The objective was to determine the prevalence and epidemiological determinants of intestinal parasitosis in schoolchildren from two cantons of Manabí, Ecuador. 793 stool samples were analyzed using the direct examination technique in children between the ages of 1 and 16, of either sex. A general prevalence of parasites of 44.4% (352/793) was determined. The prevalence of intestinal parasites due to helminths was 0.75%, while for protozoa, it was 44.8%. The main species found were the protozoan complex Entamoeba 34.7% (125 cases), Entamoeba coli 24.7% (89 cases) and Giardia lamblia 13.6% (49 cases), Blastocystis spp, 12.2%. The most frequent symptomatology in parasites was abdominal pain. The epidemiological determinant that had statistical significance was the intake of water from pipes, bottles and wells or rivers. Coefficient of Similarity of Sorensen was similar in four cantons, indicating the likeness in terms of parasitic species and risk factors.